Anfípodos hiperídeos (Crustacea: Peracarida) del Parque Nacional Isla del Coco, Costa Rica, Pacífico Tropical Oriental - Gasca, Rebeca (2012)
Hyperiid amphipods (Crustacea: Peracarida) of the Parque Nacional Isla del Coco, Costa Rica, Eastern Tropical Pacific. Hyperiid amphipods are one of the most frequently encountered pelagic crustaceans and among the most diverse marine zooplankters. To determine the species composition of the hyperiid amphipods dwelling in the waters around Isla del Coco National Park, Pacific Costa Rica, we analyzad 12 zooplankton samples, collected by vertical and horizontals tows with plankton net with mesh sizes of 200 and 500 microns and 49cm mouth diameter. We recorded a total of 22 species belonging to 17 genera and 12 families. A faunistic list of this group is provided together with data on their taxonomy and their distribution both in the surveyed area and in general. Most of the species recorded in this zone have been reported in previous surveys in the Eastern Tropical Pacific region and particularly in oceanic waters of Costa Rica. We found eight species representing new records for Costa Rican waters, thus increasing by 26% (to 38) the number of hyperiid species known from Costa Rica. The most frequent species were Lestrigonus shoemakeri, L. bengalensis, Hyperiodes sibaginis, and Phronimopsis spinifera. We expect that additional samplings both from surface and deep waters will expand the knowledge of the diversity of the group in this important protected area. Citation: Gasca, R. & Á. MoralesRamírez. 2012. Anfípodos hiperídeos (Crustacea: Peracarida) del Parque Nacional Isla del Coco, Costa Rica, Pacífico Tropical Oriental. Rev. Biol. Trop. 60 (Suppl. 3): 223-233. Epub 2012 Dec 01.